2020
DOI: 10.3390/jfb11040072
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Hyaluronic Acid to Modulate Oral Squamous Cell Carcinoma Growth In Vitro

Abstract: Introduction: Previous studies have demonstrated that glycosaminoglycan hyaluronic acid (HA) is capable of mediating oral tumor growth. Some clinical evidence has suggested reduced HA expression predicts poor cancer prognosis and that HA-chemotherapy conjugates may function synergistically to inhibit oral tumor growth. Other studies have found conflicting results that suggest enhanced CD44-HA-mediated growth and proliferation. Due to the lack of clarity regarding HA function, the primary goal of this study was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…The same as OPN, hyaluronan (HA) is mainly an abundant ECM component, and the HA/ CD44 axis plays a significant role in a number of biological functions, promoting tumor progression and therapeutic resistance, eventually resulting in poor prognosis (17). Basic studies have indicated that the HA/CD44 axis can lead to tumor cell migration that can promote metastasis formation in various tumors (18)(19)(20), which can lead to tumor cell migration in lung cancer (21). The HA/CD44 axis has been associated with poor prognosis and metastasis in NSCLC (22).…”
Section: Introductionmentioning
confidence: 99%
“…The same as OPN, hyaluronan (HA) is mainly an abundant ECM component, and the HA/ CD44 axis plays a significant role in a number of biological functions, promoting tumor progression and therapeutic resistance, eventually resulting in poor prognosis (17). Basic studies have indicated that the HA/CD44 axis can lead to tumor cell migration that can promote metastasis formation in various tumors (18)(19)(20), which can lead to tumor cell migration in lung cancer (21). The HA/CD44 axis has been associated with poor prognosis and metastasis in NSCLC (22).…”
Section: Introductionmentioning
confidence: 99%